2015
DOI: 10.3846/20294913.2015.1071296
|View full text |Cite|
|
Sign up to set email alerts
|

Impacts of Educational Factors on Economic Growth in Regions of China: A Spatial Econometric Approach

Abstract: Abstract. This paper investigates the impacts of educational factors on economic growth across 31 provinces during 1996 and 2010 in China. A spatial panel estimation model is applied to study the impacts of education on economic growth taking into account the spatial spillover effects in Feder model and the cumulative effect. The results reveal that (1) educational factors are significantly spatially autocorrelated. Educational factors have spatial spillover effects. Regional differences of education impacts s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…The fourth position in the ranking was taken by the D 5 variable indicating a country location in Asia or Oceania regions. This suggests that conditions similar to those in Asia or Oceania (in the period from 2002-2013) may determine the most likely positive economic growth (Lv et al [71]).…”
Section: Resultsmentioning
confidence: 99%
“…The fourth position in the ranking was taken by the D 5 variable indicating a country location in Asia or Oceania regions. This suggests that conditions similar to those in Asia or Oceania (in the period from 2002-2013) may determine the most likely positive economic growth (Lv et al [71]).…”
Section: Resultsmentioning
confidence: 99%
“…Lin [29] examined the effects of higher education curricula on the labor force and thus on economic growth in Taiwan, and found that higher education overall provided a positive and significant effect on Taiwan's economic development. Lv et al [30] took into account the spatial spillover effects across 31 provinces over the period 1996-2010 in China and found that average schooling year has a more positive effect on economic growth than capital investment and labor force. However, Benos and Zotou [3] pointed out that there is substantial publication selection bias toward a positive impact of education on growth by surveying 57 studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These issues have attracted considerable attention to regions. Currently, more researchers are focusing their efforts on studying the economic, political and social influences that regions exert over territories from different but convergent perspectives, e.g., the regional effects that the twin notions of creative class and creative capital have over territories (Florida, 2002(Florida, , 2005Florida, Mellander, & Stolarick, 2008), the economic implications of innovation and the Schumpeterian regional view (Batabyal & Yoo, 2018), the regional influence that regions exert over companies (Sucháček, Seďa, Friedrich, & Koutský, 2017), and the social factors involving educational and regional growth (Lv, Yu, Gong, Wu, & Xu, 2017).…”
Section: Introductionmentioning
confidence: 99%